2010
DOI: 10.1038/cmi.2009.111
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immune cell responses by semaphorins and their receptors

Abstract: Semaphorins were originally identified as axon guidance factors involved in the development of the neuronal system. However, accumulating evidence indicates that several members of semaphorins, so-called 'immune semaphorins', are crucially involved in various phases of immune responses. These semaphorins regulate both immune cell interactions and immune cell trafficking during physiological and pathological immune responses. Here, we review the following two functional aspects of semaphorins and their receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 93 publications
5
55
0
Order By: Relevance
“…The MV gp complex displayed on the MV-DC/T-cell interface essentially, yet not fully determined IS destabilization and thus, other molecules, potentially including SEMA receptors are likely to be involved also. The important role of the plexA1/NP-1 complex in regulating immune functions has been documented because their ligands determine whether they functionally support (by selfinteraction) or rather contribute to termination of (by SEMA3A interaction) the IS [22,23,44]. The importance of the ligandbinding NP-1 in the IS has been established in murine and human systems [32,45], and we now confirmed that, similar to the murine system, plexA1 is an important component of IS function (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The MV gp complex displayed on the MV-DC/T-cell interface essentially, yet not fully determined IS destabilization and thus, other molecules, potentially including SEMA receptors are likely to be involved also. The important role of the plexA1/NP-1 complex in regulating immune functions has been documented because their ligands determine whether they functionally support (by selfinteraction) or rather contribute to termination of (by SEMA3A interaction) the IS [22,23,44]. The importance of the ligandbinding NP-1 in the IS has been established in murine and human systems [32,45], and we now confirmed that, similar to the murine system, plexA1 is an important component of IS function (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…ligands determine whether they functionally support (by selfinteraction) or rather contribute to termination of (by SEMA3A interaction) the IS [22,23,44]. The importance of the ligandbinding NP-1 in the IS has been established in murine and human systems [32,45], and we now confirmed that, similar to the murine system, plexA1 is an important component of IS function (Fig.…”
supporting
confidence: 80%
“…These are activating receptors characterized by immunoreceptor tyrosine-based activating motifs in their cytoplasmic domain (Fc␥RIIC, Fc␣R, Fc⑀RI) or pairing with an immunoreceptor tyrosine-based activating motif-containing transmembrane adaptor proteins for signaling (Fc␥RIIIA), which trigger phagocytosis and immune complex clearance, inflammatory cytokine production, antibody-dependent cellular cytotoxicity, and respiratory burst. 43 Hypoxic up-regulation of other genes encoding Ig family members, such as BDCA3, LILRA2, and SEMA4D, 35,44,45 was also observed. These molecules modulate DC maturation, immunogenicity, cooperation with T cells, and proinflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 98%
“…A case in point is semaphorin 4a (SEMA4a), which was found to have strong protective effects against beta cell lipotoxic insults, but actually promoted beta cell death under other conditions [4]. Members of the semaphorin family were originally discovered as repulsive axon guidance cues, but SEMA4a also plays important roles in the immune system, where it is expressed on the membrane of dendritic cells and interacts with T cell surface receptors to provide co-stimulation in T helper type 1 cell differentiation [20]. However, as is the case for OLFM1, SEMA4a had not previously been associated with beta cell function, which illustrates the power of non-biased efforts such that by Yang et al to identify entirely novel factors that contribute to beta cell survival.…”
Section: Gfpmentioning
confidence: 99%